Biofilm-inspired Amyloid-Polysaccharide Composite Materials. (June 2022) - Wei, Shicao; Li, Yingfeng; Li, Ke; Zhong, Chao
Highlights: Biofilm-inspired composites with molecular interaction and functionality Functional composite coatings with excellent environmental resistance Functional composite coatings for device fabrication Multi-component composites enabled by nanoparticle conjugation Abstract: Natural materials can inspire the design of functional structures and sustainable materials. Bacterial biofilms formed by polymicrobial cultures typically comprise a robust interwoven fibrous network made of proteins and exopolysaccharides, protecting the cells trapped inside against various environmental stressors. Inspired by these structures, we report an amyloid-polysaccharide composite matrix using the building block of Escherichia coli biofilms (CsgA) and chitin, the second most abundant polysaccharide. We chose these two substances to mimic the main components of biofilms and combine the toughness of polysaccharide fibers and the functionality of amyloid fusion proteins to produce a new functional hybrid material. Due to the chitin-binding domain and other functional tags, the chitin-amyloid composite matrix exhibited good molecular interaction and functionality, which formed a coating on the material surface and was made into a freestanding film. With the help of this composite coating, we adhered inorganic materials onto various material surfaces. The ability to interact with inorganic materials allows this new material to be applied to electronics and organic-inorganic interfaces, and the freestanding films provide an opportunity for fabricating intelligent materials or wearable electronic devices. Additionally, these biopolymer ingredients may offer a low-cost and environmentally-friendly bio-based alternative to industrial polymers or plastics in consumer products. Graphical Abstract: Graphical Abstract Image, graphical abstract .